FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKSI PADI DI KECAMATAN SINE KABUPATEN NGAWI - Aprilian , Renggo; Parikesit Penangsang (Jurnal Nirta : Inovasi Multidisiplin, 2025)
This study aims to analyze the factors influencing rice production in Tulakan Village, Sine District, Ngawi Regency during the period of 2015–2024. The research focuses on three key production inputs: land area, labor, and fertilizer usage. The study employs a quantitative descriptive approach using secondary data obtained from the Department of Food Security and Agriculture of Ngawi Regency. The data were analyzed using multiple linear regression assisted by SPSS software.The results indicate that simultaneously, land area, labor, and fertilizer significantly affect rice production. Partially, land area has a positive and significant influence, while labor and fertilizer show a negative effect, with varying degrees of statistical significance. The coefficient of determination (R²) of 0.802 suggests that 80.2% of the variance in rice production can be explained by the independent variables in this model, while the remaining 19.8% is influenced by other external factors not included in this study.The study concludes that optimizing land area is a crucial factor in increasing rice yields. Meanwhile, labor efficiency and fertilizer application require further evaluation to ensure they contribute more positively to productivity. These findings are expected to provide valuable insights for local pimprove agricultural performance.